THE IMPACT OF TEACHERS’ ATTITUDE ON STUDENT BEHAVIOR AND ACHIEVEMENT - Abduqahhorova Oyazimxon Abdulxafiz Qizi; Umaraliyeva Munojatxon (Лучшие интеллектуальные исследования, 2024)
This article is devoted to analyzing how the teacher affects students' success and behavioral development in grades kindergarten through fifth. It investigates how much teachers' attitudes play a role in children's achievement and forming their behavior to measure academic achievement and behavior of children in kindergarten through fifth grade and also analyzes the relationship between children’s behavior and achievement and teacher attitudes.